HUBUNGAN ANTARA SELF EFFICACY DAN SELF REGULATION LEARNING DENGAN KECENDERUNGAN PERILAKU PROKRASTINASI AKADEMIK PADA PESERTA DIDIK SMK - Roro Kurnia Nofita Rahmawati (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2019)
This study aims to determine the relationship between self-efficacy and self regulation learning with academic procrastination behavior tendency in senior high school students. Subjects in this study were 89 students of class X SMKN 3 Pamekasan 2017-2018 school year . Regression analysis showed price F = 47.730 , p = 0.000 ( p ≤ 0.01 ), which means there is a very significant correlation jointly between self-efficacy and self regulation learning with academic procrastination behavior tendency in senior high school students , the results of the partial regression analysis shows the price t = -3.320 and r partial -0.337, p = 0.001 (p ≤ 0.05 ), which means there is a very significant negative correlation between self-efficacy and academic procrastination, partial analytical results indicate the price t = -4.277 and -0.419 partial r with p = 0.000 ( p ≤ 0.01), which means there is a very significant negative correlation between self-regulation learning with academic procrastination